A Proposal for Marketing Applied Research in Science and Applied Colleges at the Yemeni Universities and Using it in Community Service and Development - Eftehan Abdu Frhan Saif Almikhlafi; Khaled Hassan ali Alhariry (University of Science and Technology, Yemen, 2017)
This study aimed to propose a set of elements and mechanisms of marketing applied research in the Yemeni universities and ways of using such research to support community development. This can be done by assessing the extent of interest in the marketing of applied research and making use of them to serve and community development in the science and applied colleges at the Yemeni government universities, and determining the main obstacles in this regard from the point of view the study sample. The study sample included (287) individuals selected from teachers and researchers at the science and applied colleges in some Yemeni government universities, and research centers affiliated to them. The researchers adopted the descriptive and analytical approach, and designed a questionnaire to gather primary data from the study sample. The researchers used some appropriate statistical methods to analyze the study data and test hypotheses. The study results showed that g science and applied colleges in the Yemeni universities do not pay enough attention to marketing applied scientific research, and to using such research in community service and development. The participants of the study indicated the presence of many obstacles to marketing of applied scientific research in the Yemeni universities. The results also showed that there were no statistically significant differences in the assessments of the study sample regarding the lack of attention paid by scientific and applied colleges in the Yemeni public universities to marketing of their scientific and applied research due to these variables (type, academic degree, and applied colleges) of the study sample individuals. The study concluded by providing a proposal covering some elements and mechanisms to be used for marketing applied researches of the science and applied colleges at the Yemeni Universities and to use them in community service and development. It also provided recommendations regarding the requirements of successful implementation for this proposal in practice. Keywords: science and applied colleges, applied research, marketing research